Study on influence of polymer and surfactant on in vitro performance of biodegradable aqueous-core nanocapsules of tenofovirdisoproxil fumarate by response surface methodology - Grandhi Srikar; Avula Prameela Rani
The major objective of this study was to investigate the effect of biodegradable polymer type and surfactant concentration on various characteristics viz. particle size, entrapment efficiency and drug release rate constant of aqueous core nanocapsules (ACNs) containing tenofovirdisoproxil fumarate. In this study, the nanocapsules were prepared by modified multiple emulsion technique with biodegradable polymers viz. poly(lactide-co-glycolide) of two different grades (PLGA RG502H and PLGA RG503H) and poly lactic acid (PLA R203H); and the surfactant employed was span 80. The experiments were designed under response surface methodology by employing the Design Expert software. Entrapment efficiency, particle size and drug release rate constant were taken as response variables. The prepared nanocapsules were subjected to characterization studies and the obtained results were statistically analyzed by Analysis of Variance (ANOVA) for response surface 2-Factorial Interaction model. ANOVA studies showed that the influence of both factors on all the response variables were significant at p<0.05. The optimized formulation was found to have the entrapment efficiency of 71.58%, particle size of 252.41 nm and the drug release rate constant of 0.045 h-1; thus, indicating that the ACNs were obtained with finest characteristics. SEM studies showed that the particles were spherical.